2009
DOI: 10.1093/sleep/32.3.361
|View full text |Cite
|
Sign up to set email alerts
|

Airway Dilator Muscle Activity and Lung Volume During Stable Breathing in Obstructive Sleep Apnea

Abstract: study Objectives: Many patients with obstructive sleep apnea (OSA) have spontaneous periods of stable flow limited breathing during sleep without respiratory events or arousals. In addition, OSA is often more severe during REM than NREM and more severe during stage 2 than slow wave sleep (SWS). The physiological mechanisms for these observations are unknown. Thus we aimed to determine whether the activity of two upper airway dilator muscles (genioglossus and tensor palatini) or end-expiratory lung volume (EELV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
107
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 148 publications
(114 citation statements)
references
References 31 publications
6
107
1
Order By: Relevance
“…We therefore propose that on arousal there is preferential or more prolonged activation of both inspiratory and expiratory (tonic) component of upper airway dilator muscles, such that either the critical ratio of dilator to pump muscle activity is maintained despite a period of relative hypocapnia, or that expiratory airway collapse is prevented. Consistent with this idea, our own prior study of naturally occurring respiratory events in OSA patients also showed marked dilator muscle activation at the termination of respiratory events with arousal and no subsequent period of reduced activity during the next event (28). In fact, dilator muscle activity often ramped up over the course of respiratory events (see Figure 4 in Reference 28) as did the negative epiglottic pressure swings raising doubt over whether the hyperventilation at arousal was truly excessive (reduced CO 2 or respiratory drive below the level present on the initial event).…”
Section: Do Arousals Predispose To Further Obstructive Events?supporting
confidence: 69%
“…We therefore propose that on arousal there is preferential or more prolonged activation of both inspiratory and expiratory (tonic) component of upper airway dilator muscles, such that either the critical ratio of dilator to pump muscle activity is maintained despite a period of relative hypocapnia, or that expiratory airway collapse is prevented. Consistent with this idea, our own prior study of naturally occurring respiratory events in OSA patients also showed marked dilator muscle activation at the termination of respiratory events with arousal and no subsequent period of reduced activity during the next event (28). In fact, dilator muscle activity often ramped up over the course of respiratory events (see Figure 4 in Reference 28) as did the negative epiglottic pressure swings raising doubt over whether the hyperventilation at arousal was truly excessive (reduced CO 2 or respiratory drive below the level present on the initial event).…”
Section: Do Arousals Predispose To Further Obstructive Events?supporting
confidence: 69%
“…During respiratory events in REM sleep, the tonic activity of the GGM is reduced even below the level during respiratory events in non-REM sleep phase 2. However, some subjects, despite activating their GGM, are not able to stabilise their breathing during sleep [59].…”
Section: Non-anatomical Traitsmentioning
confidence: 99%
“…10 Second, a brisk ventilatory response can occur with arousal, which could perpetuate fluctuations in CO 2 and lead to respiratory control instability. 5,6,11,12 Lastly, periods of breathing stability during sleep, mediated by an increase in the arousal threshold and increased pharyngeal dilator muscle activation, 13,14 occur intermittently in most patients with OSA. 4 Thus, waking up prematurely to a relatively modest level of airway narrowing can limit the ability to build up sufficient respiratory stimuli to recruit the pharyngeal dilator muscles to open the upper airway, thereby achieving breathing stability.…”
Section: Introductionmentioning
confidence: 99%